Strategi Pengenalan Huruf Hijaiyah pada Anak Usia Dini dengan Metode Anak Surga - Ayuk Nur Lita Indriani; Fathur Rohman (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
This research is motivated by the lack of interest of early childhood in reading the Qur'an, especially in the introduction of basic hijaiyah letters. One of the factors that influences the interest in learning the Qur'an in early childhood is the right learning method. In the AGA method, there are games that make early childhood happy with the method. So researchers are interested in the AGA method to be used as a method for introducing hijaiyah letters. This study aims to explain the strategy for introducing hijaiyah letters to early childhood with the Anak Surga (AGA) method. The approach applied is a qualitative approach with data collection techniques including observation, interviews, and documentation. The research subjects consisted of AGA teachers and students involved in learning with the Anak Surga (AGA) method. The results of this study indicate that the use of the Anak Surga (AGA) method has a very important role in helping to increase interest in reading the Qur'an for early childhood. With a six-step method, namely brain gymnastics, remedial, reading modules, drilling, writing and games. This finding indicates that the use of the AGA method has been adjusted to the development of early childhood, so it is very appropriate to help improve children in recognizing hijaiyah letters.